The subalpine and alpine vegetation of the Georgian Caucasus - a first ethnobotanical and phytosociological synopsis - Nakhutsrishvili, George; Batsatsashvili, Ketevan; Bussmann, Rainer W; Ur Rahman, Inayat; Hart, Robbie E; Haq, Shiekh Marifatul (Ethnobotany Research and Applications, 2022)
Background: The Republic of Georgia is part of the Caucasus biodiversity hotspot, and human agricultural plant use dates back at least 6000 years. Over the last years lots of ethnobotanical research on the area has been published. In this paper we analyze the use of food plants in the 80% of Georgia not occupied by Russian forces. We hypothesized that, (1) given the long tradition of plant use, and the isolation under Soviet rule, plant use both based on home gardens and wild harvesting would be more pronounced in Georgia than in the wider region, (2) food plant use knowledge would be widely and equally spread in most of Georgia, (3) there would still be incidence of knowledge loss despite wide plant use, especially in climatically favored agricultural regions in Western and Eastern Georgia. The alpine vegetation of the Caucasus hotspot has fascinated botanists for centuries. Given the very complicated biogeographic setting, a concise classification of vegetation communities has however eluded science so far. Methods: The present work, based on 619 plots, is the first study to attempt a concise phytosociological classification. Even given this large number of samples a complete vegetation classification still proved difficult, and more releveés are needed for a detailed assessment, following Braun-Blanquet. It is also the first attempt to give an overview on plant uses in the alpine and subalpine areas of Georgia. For plant uses we employed the very large dataset that we gathered all over Georgia interviewing over 300 participants from 2014-2019. For the vegetation analysis we employed traditional phytosociological table work combined with an analysis based on species composition, coverage and abiotic factors using "R", compared to a classification using "Twinspan". From 2013 to 2019 we also interviewed over 380 participants in all regions of Georgia not occupied by Russian forces. All interviews were carried out in the participants’ homes and gardens by native speakers of Georgian and its dialects (Imeretian, Rachian, Lechkhumian, Tush, Khevsurian, Psavian, Kakhetian), other Kartvelian languages (Megrelian, Svan) and minority languages (Ossetian, Ude, Azeri, Armenian, Greek). Results: We found that 183 species of the subalpine and alpine flora, representing about 33% of all species encountered in the vegetation survey, had reported uses. The usage of alpine and subalpine species in Georgia is mostly focused on the use of the plants as fodder, which is unsurprising. Green crops such as Lactuca sativa, Phaseolus vulgaris, Ocimum basilicum, Mentha x piperita, Allium cepa, and Artemisia dracunculus are grown virtually everywhere. Cucurbita pepo, Cucumis sativus, Solanum melongena, and Zea mays, all introduced species, were discovered to be popular elements in local cuisine. In human and veterinary medicine, however, Matricaria chamomilla, Berberis vulgaris, and Juniperus hemisphaerica are still used. There are two vegetation classes: Bromopsis variegatae - Festucaetea ovinea (Class. nov.) (Subalpine pastures), which has seven orders and twelve alliances/eighteen associations, and Sympoholoma graveolensis - Saxifragetea exaratae (Class. nov.) (Alpine pastures), which has one order, two alliances, and four associations. Conclusions: The alpine and subalpine vegetation of the Greater Caucasus and its uses were assessed in detail for the first time, highlighting the still existing gaps in both phytosociological and ethnobotanical work. Given the establishment of borders in post-soviet independence, it will be interesting to see how long this original cross-cultural knowledge will remain, given that the actual use of the traditional knowledge, as well as cross-border high altitude pastoralism are declining. Keywords: Republic of Georgia, Caucasus, Traditional Knowledge